Curriculum, teaching and interdiscipline. - (:unkn) unknown (Universidad Nacional de Rosario, 2017)
This paper makes visible the problems around teachers’ knowledge regarding teaching and content management. It shows a proposal of Interdisciplinary Core Content (ICC) in the Ministry of Education of Santa Fe, Argentina. Aided by Shulman’s questions and his missing paradigm, we formulate our own questions about the relationship between content and teaching: why is teaching a content-free domain? If it is a problem of curriculum and didactics, what can we do with these dissociated fields of study which need to keep coexisting in the same environment? Addressing the curriculum-didactics tension in teaching includes the disciplinary/interdisciplinary debates to set up contents. In the curriculum-society relationship, ICC are developed taking the social issues proper of each context about Human Rights, Climate Change, Violence, Energy, Culture, the Space, Nutrition and Health as starting points. As a micro-level curriculum policy, the selection and sequencing of content transforms into a teaching problem. While at the meso-level dialogue, the relationship between curriculum and didactics is strengthened. The event question about what is going on? shows its genealogical nature. This teaching scenario is established based on the didactic triad, conditioned by the institutional context and configured by the special characteristics of each one of the members of the class.
Keywords: Teaching; Curriculum; Didactics; Complementary relationship